La participación ciudadana en el distrito metropolitano de Quito, zona centro año 2015 - Calva Cumbicus, María Ofelia (2017)
The following essay demonstrates an analysis of the participation of citizens in the current democratic representations and the challenge to improve this liberal democracy through the political involvement of citizens in their communities. For this, we will turn to the new juridical frame that includes the participation of citizens which was established in the Constitution of the Republic in the year 2008, created in Montecristi. We will analyze the possibilities of a consolidated citizen participation in the context of the Alianza País government and its own promotion in the decentralized autonomous governments. For this we will use as an example the case of the Metropolitan District of Quito Zona Centro in the year 2015